HIJAB SEGITIGA AKUNTAN UNTUK MELAWAN KORUPSI - Sari, Arista Fauzi Kartika (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
This article aims to create a concept can be used by accountants to fight corruption by a hijab. The concept consists of three things; spiritual, ethical and love. They are an influential interconnected with each other and form a Hijab Triangle. Hijab Triangle serves as a shield modern accounting value, ie materialistic and egoistic to affect inward accountants in soul and thought. It can cause an accountants doing corruption. Hijab triangle can also make accountants more